Timing of subduction initiation, arc formation, ophiolite obduction and India–Asia collision in the Himalaya - Searle, M (Geological Society of London, 2018)
Reconstruction of the Western Himalaya requires three subduction systems operating beneath the Spong arc, Dras–Kohistan arc and the Asian continent during the Late Cretaceous–Paleocene. The timing of the closure of the Neo-Tethys Ocean along the Indus Suture Zone (ISZ) in Ladakh and south Tibet has been proposed to be as old as c. 65 Ma and as young as c. 37 Ma. The definition of the India–Asia collision can span >15 myr from the first touching of Indian continental crust with Asian crust to the final marine sedimentation between the two plates. There is good geological evidence for a Late Cretaceous–Early Paleocene phase of folding, thrusting and crustal thickening of Indian Plate shelf carbonates associated with obduction of ophiolites. There is no geological evidence of any oceanic ‘Greater Indian Basin’ separating the northern Tethyan and Greater Himalaya from India. There is clear evidence to support final ending of marine sedimentation along the ISZ at 50 Ma (planktonic foraminifera zone P7–P8). There is no evidence for diachroneity of collision along the Pakistan–Ladakh–South Tibet Himalaya. The timing of ultrahigh-pressure metamorphism cannot be used to constrain India–Asia collision, and the timing of high-grade kyanite- and sillimanite-grade metamorphism along the Greater Himalaya can only give a minimum age of collision.